Legal Status of Electronic Money in Ukraine - Dyakovych, Myroslava M.; Mykhayliv, Mariya O. (International Journal of Criminology and Sociology, 2021)
The lack of a unified theoretical position on the definition of electronic money, insufficient understanding of their technical, economic, and legal nature, the discrepancy in the legal regulation of the circulation of such money in different countries is conditioned by the novelty of the institution of electronic money. In turn, due to the rapid progress, the issue of electronic money is becoming increasingly relevant, attracting the attention of lawyers, economists, and society as a whole. The purpose of this study is to analyse the legal status of electronic money, its advantages and disadvantages, considering the practice of the European Union in this matter. The study used a complex of philosophical and worldview general scientific and special scientific methods. The formal-logical method was used to define the basic concepts and legal categories related to the analysis of the legal status of electronic money in Ukraine. The historical method was used to highlight the process of development and establishment of legal regulation of electronic money in Ukraine. The method of systems analysis allowed to identify and formulate the main conclusions and recommendations for increasing the efficiency of cooperation between Ukraine and the European Union in the field of legal regulation of electronic money. Furthermore, when determining the legal status of electronic money, it is important to consider the legislation of the European Union. The study also analyses the differences in the legal status of electronic money from non-cash, virtual, and digital money.